Ab initio calculations of structural, electronic, magnetic and thermoelectric properties of Cr1−xAlxP. (2nd November 2021) - El haoua, M.; Azouaoui, A.; Salmi, S.; Benzakour, N.; Hourmatallah, A.; Bouslykhane, K.
ABSTRACT: In the present study, the structural, electronic, magnetic and thermo electric (TE) properties of C r 1 − x A l x P ( 0 ≤ x ≤ 1 ) have been performed using first principle calculations based on the density functional theory (DFT) and BoltzTraP code. The obtained results show that C r P is ferromagnetic with a lattice constant of 5.41 Å and the magnetic moment of C r equal 3µB . Density of states (DOS) of C r 1 − x A l x P show a metallic behavior for x = 0, half metallic for x = 0.25, 0.5 a n d 0.75, and semiconductor for x = 1 . The TE properties such as Seebeck coefficient, electrical conductivity, electronic thermal conductivity, power factor, figure of merit and electronic specific heat are calculated. Negative values of Seebeck coefficient indicate that C r 1 − x A l x P are n-type carriers. The obtained results show that doping of C r P with A l has a great influence on the thermoelectric properties.